A Langendorff-like system to quantify cardiac pump function in adult zebrafish - Hong Zhang; Alexey V. Dvornikov; Inken G. Huttner; Xiao Ma; Celine F. Santiago; Diane Fatkin; Xiaolei Xu (The Company of Biologists, 2018)
Zebrafish are increasingly used as a vertebrate model to study human cardiovascular disorders. Although heart structure and function are readily visualized in zebrafish embryos because of their optical transparency, the lack of effective tools for evaluating the hearts of older, nontransparent fish has been a major limiting factor. The recent development of high-frequency echocardiography has been an important advance for in vivo cardiac assessment, but it necessitates anesthesia and has limited ability to study acute interventions. We report the development of an alternative experimental ex vivo technique for quantifying heart size and function that resembles the Langendorff heart preparations that have been widely used in mammalian models. Dissected adult zebrafish hearts were perfused with a calcium-containing buffer, and a beat frequency was maintained with electrical stimulation. The impact of pacing frequency, flow rate and perfusate calcium concentration on ventricular performance (including end-diastolic and end-systolic volumes, ejection fraction, radial strain, and maximal velocities of shortening and relaxation) were evaluated and optimal conditions defined. We determined the effects of age on heart function in wild-type male and female zebrafish, and successfully detected hypercontractile and hypocontractile responses after adrenergic stimulation or doxorubicin treatment, respectively. Good correlations were found between indices of cardiac contractility obtained with high-frequency echocardiography and with the ex vivo technique in a subset of fish studied with both methods. The ex vivo beating heart preparation is a valuable addition to the cardiac function tool kit that will expand the use of adult zebrafish for cardiovascular research.